(3OjhGf CMeO GdYWGQs - (3CMeO Hf eMeO GdYWGQ Hf Ydj GdMSjfj GdHZOGOj,J (B1215 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI bO LeYJ gPG GdOjhGf hLYdJg aUdjf GdChdi aj Phj GdYUeI, hGdKGfj ajef ShGge ef GdYdeGA hGdSGOGJ hCeKGdge hPdc MSHeG Cecffj LeYg s
(3BNQgG (B:s
(3bdJ(B: (3de bO CXdeJ bGd(B: (3aCQN Mjf eGJ GdegOj eGJ GdYde hbGd aj UOQ cJGH GdSjO YHOGddg GdaNQj GdCYQLj s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3aj ChdgG JQLeI dCMeO GdYWGQ hCNjg EHQGgje GdYWGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B232s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B20 s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI HGdfLa (B(293) s
Keywords: (3GdCOHs